Sawur Or Sawer Rite: the Perspective of Death Javanese-Sundanese Tradition In Catholic Church - Nikasius Jatmiko (International Journal of Indonesian Philosophy & Theology, 2022)
Death is a certainty that humans cannot avoid. Everyone will face this event without exception. The difference lies in respecting the corpse before it is buried or cremated. Each region has its peculiarities in building a death ceremony. Culture plays a significant role in shaping the death ceremony based on local wisdom. These rites lead to the same goal: placing death as a noble act. This study aims to preserve and explore cultural wealth that is becoming extinct according to the times. These methods show that humans have a high value and dignity compared to other creations, even though they have died. This value is maintained through various very noble awards. Javanese and Sundanese have similarities in respecting the bodies to be buried. The ritual of sawer or sawur is a value that distinguishes it from other cultures. Local wisdom is still maintained, even though modernity has begun to erode it.